Does accelerating access to higher education lower its quality? The Australian experience - Pitman, Tim; Koshy, Paul; Phillimore, John (Routledge, 2015)
In the pursuit of mass higher education, fears are often expressed that ‘quantity’ increases at the expense of ‘quality’ (Hawkins & Neubauer, 2011). The case of the Australian higher education sector is salient, for in many respects it has led the way, internationally, in increasing access through both domestic and international channels. This paper examines the recent introduction of a demand-driven funding system (DDFS) for domestic enrolments in Australia to determine the impact of the subsequent expansion in domestic student numbers on overall domestic performance.